VARIABILITY AND CORRELATION STUDIES FOR GRAIN PHYSICOCHEMICAL CHARACTERISTICS OF RICE (ORYZA SATIVA L.) - VIJAY KUMAR (The Bioscan, 2015)
The analysis revealed significant differences among the genotypes for all the 10 quality traits indicating that sufficient variability is present in the material involved in the study.The high PCV was recorded for grain L/B ratio (17.54%, 34.21% and 8.64%) and gelatinization temperature (27.70%, 31.79% and 17.92%) in land races, new plant types and japonicas, respectively. High heritability (broad sense) along with high genetic advance as per cent of mean was observed for L/B ratio (34.60, 69.92 and 16.39) and gelatinization temperature (41.91, 62.26 and 28.13), respectively for land races, new plant types and japonicas. Grain length showed significant positive correlation with L/B ratio (0.851, 0.956) and grain elongation (0.832, 0.934) in land races and new plant types,while significant positive correlation with L/B ratio (0.748) 1000-grain weight (0.437) and amylose content (0.322)in japonica. Grain width showed significant positive correlations with 1000-grain weight (0.416) and protein content (0.448) in land races; with grain thickness (0.889, 0.563) and 1000-grain weight (0.331, 0.326) in newplant types and japonicas. Highest average iron content(15.44 μg/g) was estimated in new plant types, while zinc content was highest in land races (7.06 μg/g).This indicated that grain length, grain width and gelatinization temperature can be used for the improvement in grain quality in rice.